Upaya Penurunan Angka Stunting pada Balita Melalui Deteksi Dini dan Intervensi Nutrisi - Ni’matul Fauziah; Ika Hepi Maidayanti; Heni Amilia Putri; Brelianti Nevy Tyara C. P.; Chindy Elsa Ramadhani; Ferdiana Putri Gita V. (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Stunting is a condition that occurs due to a lack of nutritional intake over a long period of time, thus inhibiting a child's growth. As the next generation of the nation, children need special attention in terms of their growth and development. Fulfillment of nutrition must begin before pregnancy, continued with exclusive breastfeeding after the baby is born, and continued with balanced nutritious food according to the stage of growth. This study was conducted using a literature study method to collect data related to efforts to reduce stunting rates in toddlers. The results of the study showed that community education through counseling and health education can increase understanding of nutrition and good parenting patterns. In addition, programs such as providing eggs in villages and the involvement of integrated health post cadres in early detection have also proven effective in reducing stunting rates in toddlers.